(untitled) (Research, Society and Development, 2020)
With the growth of the elderly population, there was an increase in cases of chronic diseases, including prostate câncer. Among the treatments, surgery can have side effects that influence the quality of sexual life. Therefore, it is necessary to investigate these patients. The aim of the study was to analyze the quality of sexual life in patients who underwend prostatectomy. The study refers to an integrative literature review , in which the insertion criteria were: articles in full that highlighted the quality of sexual life in post-prostatectomy patients published between 2015 and 2020, in the databases of SCIELO and LILACS. For the construction of the findings, 7 articles were selected because they meet the eligibility criteria. Such evidence indicates that reduced libido and erectile dysfunction can contribute to poor sexual quality of life. Information about the patients’ chance of recovering from natural erections has often been passed on to them so that, together with their sexual partners, they allow themselves to face and adapt to this new reality. Although erectile dysfunction is highly prevalent among men who have undergone surgery, in some cases there is a deficit in the preoperative discussion. As a result, the quality of sexual life after prostatectomy is compromised due to impacts on sexuality, with repercussions in different spheres of life. It is still a little discussed topic with patients and there is a lack of evidence on the subject. This study aims to open space for planning further studies to better benefit post-prostatectomy patients.